Role of GenoType® Mycobacterium Common Mycobacteria/Additional Species Assay for Rapid Differentiation between Mycobacterium tuberculosis Complex and Different Species of Non-tuberculous Mycobacteria - Singh, Amresh Kumar; Maurya, Anand Kumar; Umrao, Jyoti; Kant, Surya; Kushwaha, Ram Awadh Singh; Nag, Vijaya Laskshmi; Dhole, Tapan N (Journal of Laboratory Physicians, 2013)
Background:Mycobacterium tuberculosis complex (MTBC) and non-tuberculous mycobacteria (NTM) may or may not have same clinical presentations, but the treatment regimens are always different. Laboratory differentiation between MTBC and NTM by routine methods are time consuming and cumbersome to perform. We have evaluated the role of GenoType® Mycobacterium common mycobacteria/additional species (CM/AS) assay for differentiation between MTBC and different species of NTM in clinical isolates from tuberculosis (TB) cases.Materials and Methods: A total of 1080 clinical specimens were collected from January 2010 to June 2012. Diagnosis was performed by Ziehl-Neelsen staining followed by culture in BacT/ALERT 3D system (bioMerieux, France). A total of 219 culture positive clinical isolates (BacT/ALERT® MP cultures) were selected for differentiation by p-nitrobenzoic acid (PNB) sensitivity test as and BIO-LINE SD Ag MPT64 TB test considering as the gold standard test. Final identification and differentiation between MTBC and different species of NTM were further confirmed by GenoType® Mycobacterium CM/AS assay (Hain Lifescience, Nehren, Germany).Results: Out of 219 BacT/ALERT® MP culture positive isolates tested by PNB as 153 MTBC (69.9%) and by GenoType® Mycobacterium CM/AS assay as 159 (72.6%) MTBC and remaining 60 (27.4%) were considered as NTM species. The GenoType® Mycobacterium CM/AS assay was proved 99.3% sensitive and 98.3% specific for rapid differentiation of MTBC and NTM. The most common NTM species were; Mycobacterium fortuitum 20 (33.3%) among rapid growing mycobacteria and Mycobacterium intracellulare 11 (18.3%) among slow growing mycobacteria.Conclusion: The GenoType® Mycobacterium assay makes rapid and accurate identification of NTM species as compared with different phenotypic and molecular diagnostic tool and helps in management of infections caused by different mycobacteria.
Keywords: GenoType® Mycobacterium common Mycobacteria/additional species assay; M. tuberculosis complex; minimumT cell receptor; non-tuberculous Mycobacteria